Training Introduction to Simple Robots for Kindergarten Child as a Tool in Improving Children’s Psychomotoric Abilities - Ratna Mayasari; Sri Astuti; Ridha Muldina Negara; Rohmat Tulloh; Dwi Andi Nurmantris (Journal of Innovation and Community Engagement, 2025)
Early childhood education plays an important role in forming the basis of children's development, including their psychomotor development. Early childhood education (PAUD) teachers at PG & TKIT Little Moslem have a big responsibility in creating a learning environment that supports children's holistic development. However, they often face challenges in choosing effective learning methods, especially when it comes to integrating modern technology. In this context, the use of robotics as a learning aid offers great potential for improving children's psychomotor abilities at an early age. Training on introducing simple robots to teachers at PG & TKIT Little Moslem is a relevant solution to overcome this problem. This training aims to provide knowledge, skills, and understanding of the basic concepts of robotics and how to integrate them into early childhood learning activities. In this way, teachers can create more engaging, interactive, and effective learning experiences for their students.